2017
DOI: 10.1016/j.appet.2017.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Presenting a food in multiple smaller units increases expected satiety

Abstract: Presentation of the same amount of a food in multiple smaller units (‘segmentation’) has been shown to reduce food intake and increase estimates of the amount of food consumed. However, this effect has been demonstrated for ad libitum food intake only. In the majority of cases, meals are not consumed ad libitum, but are pre-selected and consumed in their entirety, Expected satiety (ES; the anticipated capacity of a portion of food to relieve hunger between meals) is an excellent predictor of portion size selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Childhood is a critical period in the development of obesity [ 77 ]. The feeding practices that evolved across human history as effective parental responses to the threat of food scarcity can, when combined with infants’ unlearned preferences and predispositions, promote overeating and overweight given the current availability of calorie-dense food [ 77 ].…”
Section: Obesogenic Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood is a critical period in the development of obesity [ 77 ]. The feeding practices that evolved across human history as effective parental responses to the threat of food scarcity can, when combined with infants’ unlearned preferences and predispositions, promote overeating and overweight given the current availability of calorie-dense food [ 77 ].…”
Section: Obesogenic Environmentmentioning
confidence: 99%
“…Childhood is a critical period in the development of obesity [ 77 ]. The feeding practices that evolved across human history as effective parental responses to the threat of food scarcity can, when combined with infants’ unlearned preferences and predispositions, promote overeating and overweight given the current availability of calorie-dense food [ 77 ]. Dietary behaviours thought to contribute to childhood obesity include appetitive traits such as: difficulty in matching the intake of energy to needs, a behaviour known as low responsiveness to internal satiety signals; high responsiveness to external food cues; high subjective reward experienced when eating liked foods; and preferences for energy-dense foods.…”
Section: Obesogenic Environmentmentioning
confidence: 99%
“…Por otro lado, se ha demostrado que la velocidad de ingesta de un alimento se asocia directamente con la cantidad ingerida y en forma inversa con los niveles de saciedad [24][25][26][27] . La expectativa de saciedad es mayor al presentar una comida fraccionada en múltiples porciones o platos, que en una sola unidad 28 . La once, generalmente, se presenta como un sándwich, lo cual disminuiría la expectativa de saciedad y aumentaría la velocidad de ingesta, favoreciendo un mayor consumo y menor saciedad durante o después de esta comida.…”
Section: Discussionunclassified
“…Different studies have reported the use of computer based tasks to measure food portion size related perceptions such as expected satiety [ 22 ], perceived volume [ 23 ], ideal portion size [ 24 ], portion size estimates [ 25 ], and perceived healthfulness [ 26 ], but few studies have investigated the predictive power of computer based tasks on actual behaviors and with mixed results. Wilkinson et al [ 27 ] reported that a screen-based measure of expected satiety was a good predictor of ideal portion size assessed in a computer task and of eating behaviors associated with real food, i.e., ad libitum food intake measurement.…”
Section: Discussionmentioning
confidence: 99%